Tumor necrosis factor‐α induces prostate cancer cell migration in lymphatic metastasis through CCR7 upregulation - Maolake, Aerken (Cancer Sci, 2018)
Understanding the mechanism of lymph node metastasis, a poor prognostic sign for prostate cancer, and the further dissemination of the disease is important to develop novel treatment strategies. Recent studies have reported that C‐C chemokine receptor 7 (CCR7), whose ligand is CCL21, is abundantly expressed in lymph node metastasis and promotes cancer progression. Tumor necrosis factor‐α (TNF‐α) is chronically produced at low levels within the tumor microenvironment. The aim of this study was to determine whether TNF‐α promotes prostate cancer dissemination from metastatic lymph nodes through activation of the CCL21/CCR7 axis. First, human prostate cancer cells were determined to express both TNF‐α and CCR7. Second, low concentrations of TNF‐α were confirmed to induce CCR7 in prostate cancer cells through phosphorylation of ERK. Finally, CCL21 was found to promote the migration of prostate cancer cells through phosphorylation of the protein kinase p38. Our results suggest that TNF‐α leads to the induction of CCR7 expression and that the CCL21/CCR7 axis might increase the metastatic potential of prostate cancer cells in lymph node metastasis.